2020
DOI: 10.1002/jmri.27148
|View full text |Cite
|
Sign up to set email alerts
|

MRI of the Pancreas

Abstract: MRI has played a critical role in the evaluation of patients with pancreatic pathologies, from screening of patients at high risk for pancreatic cancer to the evaluation of pancreatic cysts and indeterminate pancreatic lesions. The high mortality associated with pancreatic adenocarcinomas has spurred much interest in developing effective screening tools, with MRI using magnetic resonance cholangiopancreatography (MRCP) playing a central role in the hopes of identifying cancers at earlier stages amenable to cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 98 publications
0
19
0
Order By: Relevance
“…Harrington et al reported that small PDAC could be detected as a mass on T1WI or an MPD abnormality on MRCP. [22] Ichikawa et al demonstrated the high sensitivity and specificity of DWI for detecting PDAC. [23] Our results were consistent with these previous reports showing the usefulness of T1WI, DWI, and MRCP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Harrington et al reported that small PDAC could be detected as a mass on T1WI or an MPD abnormality on MRCP. [22] Ichikawa et al demonstrated the high sensitivity and specificity of DWI for detecting PDAC. [23] Our results were consistent with these previous reports showing the usefulness of T1WI, DWI, and MRCP.…”
Section: Discussionmentioning
confidence: 99%
“…reported that small PDAC could be detected as a mass on T1WI or an MPD abnormality on MRCP. [ 22 ] Ichikawa et al . demonstrated the high sensitivity and specificity of DWI for detecting PDAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Noninvasive medical imaging such as US, MRI, CT, and positron emission tomography (PET) can be used to assess tumor and anatomical tissue features for tumor management (55)(56)(57). Radiomics can obtain high-content information through identification, extraction, quantitation, and processing to identify imaging signatures or phenotypes.…”
Section: Imaging Diagnosis and Precision Imagingmentioning
confidence: 99%
“…However, response to RT varies significantly among individual patients and may be in part related to the unique characteristics of the PDAC tumor microenvironment, including hypoxia [2]. There is a need to develop and translate new imaging biomarkers that may predict early treatment efficacy to allow for better risk stratification and possible treatment intensification in appropriate candidates [13]. RT using high doses per fraction may be associated with rapid, immediate changes to the tumor microenvironment, including tumor cellularity and vascularity, which correlate with eventual clinical RT response [14,15].…”
Section: Introductionmentioning
confidence: 99%